2015
DOI: 10.1126/science.aaa3952
|View full text |Cite
|
Sign up to set email alerts
|

Mountain gorilla genomes reveal the impact of long-term population decline and inbreeding

Abstract: Mountain gorillas are an endangered great ape subspecies and a prominent focus for conservation, yet we know little about their genomic diversity and evolutionary past. We sequenced whole genomes from multiple wild individuals and compared the genomes of all four Gorilla subspecies. We found that the two eastern subspecies have experienced a prolonged population decline over the past 100,000 years, resulting in very low genetic diversity and an increased overall burden of deleterious variation. A further recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

40
434
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 352 publications
(504 citation statements)
references
References 57 publications
40
434
2
Order By: Relevance
“…The distribution of genetic variation along individual genomes is informative of recent inbreeding (23,24). In particular, inbred individuals are expected to have long genomic fragments with both average and low heterozygosity values, producing a bimodal distribution of variation when estimated in windows across the genome (25).…”
Section: Pattern Of Variation and Inbreeding Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of genetic variation along individual genomes is informative of recent inbreeding (23,24). In particular, inbred individuals are expected to have long genomic fragments with both average and low heterozygosity values, producing a bimodal distribution of variation when estimated in windows across the genome (25).…”
Section: Pattern Of Variation and Inbreeding Estimatesmentioning
confidence: 99%
“…Despite the difficulty in assessing the role of genetic factors in past extinctions of small populations, the causative link between low genetic and genomic variation, fitness reduction, and high extinction risk is supported by theoretical arguments and empirical evidence (24,(62)(63)(64)(65). Still, the long-term persistence of species at extremely low levels of genomic variation has also been documented (11,66).…”
Section: Conclusion and Conservation Perspectivesmentioning
confidence: 99%
“…This is akin to the approaches in (8,44) where biases to do with branch shortening and deamination errors between ancient and modern genomes are mitigated. Estimates of the variance in R A/B were obtained using 100 block jackknifes on the set of sites in C.…”
Section: (C)/ L A/b (S)mentioning
confidence: 99%
“…However, this expectation has been challenged by the realization that there are numerous examples where human mutant alleles correspond to the wild-type alleles in other mammalian species. [1][2][3][4][5][6][7] Such variants have become known as compensated pathogenic deviations (CPDs) following their original designation 5 because it is assumed that the apparently benign nature of these missense variants in non-human species is due to the coexistence of other amino-acid substitutions (AASs) that compensate for their otherwise dysfunctional consequences. Among those human mutant residues corresponding to the wild-type residue in mouse 5 are an p.(Ala53Thr) (NM_000345.3:c.157G4A) substitution at the α-synuclein (SNCA) locus reported to be associated with familial Parkinson disease; 8 the ADA-p.(Arg142Gln) (NM_000022.2: c.425G4A) causing severe combined immunodeficiency; 9 and the CFTR-p.(Phe87Leu) (NM_000492.3:c.259T4C) in the cystic fibrosis transmembrane conductance regulator gene underlying cystic fibrosis.…”
mentioning
confidence: 99%
“…Intriguingly, a different OTC variant p.(Thr125Met) associated with fatal hyperammonemia 14 was found to correspond to the wild-type allele in chimpanzees. 1,15,16 Among the CPDs identified through a comparison with the recently reported mountain gorilla genome 6 was the NPC1-p.(Asn961Ser) (NM_000271.4:c.2882A4G) that leads to Niemann-Pick disease C. 17 Finally, variants associated with ciliopathies at the BBS4 and RPGRIP1L genes associated with Bardet-Biedl and Meckel-Gruber syndromes, respectively, constitute the wild-type alleles in the genomes of several vertebrates. 7 The same study reported a de novo variant at the BTG2 locus in which the disease-associated allele corresponded to the wild-type allele in more than 50 vertebrate species.…”
mentioning
confidence: 99%